Asymmetric Electrophilic Fluorocyclization with Carbon Nucleophiles1. Issue 37 (22nd July 2013) - Wolstenhulme, Jamie R.; Rosenqvist, Jessica; Lozano, Oscar; Ilupeju, John; Wurz, Nathalie; Engle, Keary M.; Pidgeon, George W.; Moore, Peter R.; Sandford, Graham; Gouverneur, Véronique
<x xml:space="preserve">Abstract</x> Twist of 'F'ate: Various helical‐shaped fluorinated tetracyclic molecules were prepared by fluorocarbocyclization of prochiral alkenes. The development of a new class of chiral Selectfluor (1) proved instrumental in developing an asymmetric variant of this transformation. These novel chiral N‐F reagents are readily accessible by fluorine transfer from shelf‐stable N‐fluoropyridinium salts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>